Interpretasi Teologis: Injil Akan Diberitakan di Seluruh Dunia Sesudah Itu Barulah Tiba Kesudahan Dalam Matius 24:14 di Masa Pandemik Covid-19 - Stimson B. Hutagalung (Jurnal Koinonia, 2020)
This article provides a brief but comprehensive overview of the understanding of God's people about the phrase “And this gospel of the kingdom shall be preached in all the world for a witness unto all nations; and then shall the end come” during theCovid 19 pandemic where the use of technology became a necessity. The research methodology used is a qualitative analysis method through a theoretical perspective, using narrative interpretation through bible, official documents, spiritual books, andtheological journals. The results of the analysis were first, in the midst of the ongoing Covid 19 pandemic, the use of technology via the internet network with its various applications accelerates and facilitates the spread of the gospel throughout the world. Second, the method used for evangelism is to use applications such as Zoom, Google Meet, Zoho Meeting, Cisco WebEx, Join Me, Google Hangouts Meet and other applications. By using these various applications, everyone, wherever they are, even in remote villages where the internet network is available, they could attend Bible study classes and listen to sermons from various pastors from any country, thereby arousing their interest in deepening their knowledge of Jesus.